Sistem Pencatatan Akuntansi Berbasis System Application And Product In Data Processing (SAP) Pada Persediaan Barang Jadi WRG PT. Bhirawa Steel Surabaya - Maria Christina R; Wiratna Wiratna; Tjandra Wasesa; Heri Toni; Sutini Sutini; Diana Zuhro (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
With current technological developments, accounting systems are becoming increasingly complex. Companies must be able to update their work methods to improve the quality of financial reports. The company always uses an accounting system that is managed and integrated with its business. With a well-organized accounting system, it also offers good benefits for business management. Every business has several accounting systems that are interconnected and work together to achieve certain goals. In trading and manufacturing companies, inventory is one of the company's assets that can be used in the production process and then sold for profit or for use for internal purposes in the company's normal operations. Inventory is the most important key for a company, because this company has two functions, namely to determine the company's financial position and is also very influential in calculating the cost of goods sold to determine the amount of profit or loss for one season. Manufacturing Companies, hereinafter referred to as PT. Bhirawa Steel is a manufacturing company located on Jalan Margomulyo No. 6 Surabaya, which operates in the steel and iron business sector. In operational business activities, PT. Bhirawa Steel produces WRG products according to orders from customers in providing inventory of finished goods. The accounting system in recording inventory used by PT. Bhirawa Steel uses a computer program based on System Application and Product in Data Processing (SAP). Considering that inventory is an important element in company management, PT. Bhirawa Steel uses the SAP application as a means of internal control over its inventory recording.